Sumatriptan-naproxen fixed combination for acute treatment of migraine: a critical appraisal - Chaouki K Khoury; James R Couch (Dove Medical Press, 2010)
Chaouki K Khoury, James R CouchDepartment of Neurology, University of Oklahoma Health Sciences Center, Oklahoma City, Oklahoma, USAAbstract: Nonsteroidal anti-inflammatory drugs (NSAIDs), including naproxen and naproxen sodium, are effective yet nonspecific analgesic and anti-inflammatory drugs, which work for a variety of pain and inflammatory syndromes, including migraine. In migraine, their analgesic effect helps relieve the headache, while their anti-inflammatory effect decreases the neurogenic inflammation in the trigeminal ganglion. This is the hypothesized mechanism by which they prevent the development of central sensitization. Triptans, including sumatriptan, work early in the migraine process at the trigeminovascular unit as agonists of the serotonin receptors (5-HT receptors) 1B and 1D. They block vasoconstriction and block transmission of signals to the trigeminal nucleus and thus prevent peripheral sensitization. Therefore, combining these two drugs is an attractive modality for the abortive treatment of migraine. Sumatriptan–naproxen fixed combination tablet (Treximet® [sumatriptan–naproxen]) proves to be an effective and well tolerated drug that combines these two mechanisms; yet is far from being the ultimate in migraine abortive therapy, and further research remains essential.Keywords: Treximet®, sumatriptan–naproxen, migraine, treatment